Dysautonomia in Parkinson’s Disease: Impact of Glucocerebrosidase Gene Mutations on Cardiovascular Autonomic Control - Carandina, Angelica; Lazzeri, Giulia; Rodrigues, Gabriel Dias; Franco, Giulia; Monfrini, Edoardo; Arienti, Federica; Frattini, Emanuele; Trezzi, Ilaria; da Silva Soares, Pedro Paulo; Bellocchi, Chiara; Furlan, Ludovico; Montano, Nicola; et al. (Frontiers in Neuroscience, 2022)
Evidence from clinical practice suggests that PD patients with the Glucocerebrosidase gene mutation (GBA-PD) are characterized by more severe dysautonomic symptoms than patients with idiopathic PD (iPD). Therefore, an accurate assessment of cardiovascular autonomic control (CAC) is necessary to clarify the role of GBA mutations in the pathophysiology of PD. We evaluated the CAC at rest and during orthostatic challenge of 15 iPD, 15 GBA-PD and 15 healthy controls (CTR). ECG and respiration were recorded in supine position and during active standing. The analysis of Heart Rate Variability (HRV) was performed on ECG recordings using two different approaches, linear spectral analysis and non-linear symbolic analysis. GBA-PD patients presented more frequently an akinetic-rigid phenotype and cognitive disfunction than iPD patients. Both iPD and GBA-PD group were characterized by a lower spectral HRV than CTR group. At rest, the GBA-PD group was characterized by a lower parasympathetic modulation and a shift of the sympathovagal balance towards a sympathetic predominance compared to the CTR group. Moreover, the GBA-PD patients presented a lower HR increment and a lower or absent reduction of the vagal modulation in response to the active standing than iPD patients. Lastly, the cardiovascular autonomic dysfunction in PD patients was associated with longer disease duration, and with the occurrence of REM sleep behavior disorder and constipation. Our findings suggest a more severe impairment in the CAC of PD patients with GBA mutations. These results and further studies on the role of GBA mutations could allow a stratification based on cardiovascular risk in PD patients and the implementation of prevention programs.